Annealing effects on metal-ZnO interface for improvement performance of Thin-film Transistors. Issue 1731 (11th February 2015) - Dominguez, Miguel A.; Flores, Francisco; Luna, Adan; Alcantara, Salvador; Martinez, Javier; Luna-Lopez, Jose A.; Rosales, Pedro; Reyes, Claudia
ABSTRACT: In this work, the annealing effects at 180°C in Aluminum-ZnO contacts as function of time were studied. Also, the application in TFTs of ZnO films obtained at low-temperature (200°C) are presented. The ZnO films obtained by ultrasonic Spray Pyrolysis at 200 °C were deposited over Aluminum contacts on SiO2 /Si wafers to demonstrate the use of active layer in thin-film transistors. The results show that an improvement can be obtained in metal-ZnO interfaces by low-temperature annealing treatments. However, long annealing time degrade the metal-ZnO interface and may affect the electrical performance of the device.